Degree of Perceived Accent in Finnish as a Second Language for Turkish Children Born in Finland. Issue 3 (15th July 2015) - Uzal, Melike; Peltonen, Teemu; Huotilainen, Minna; Aaltonen, Olli
<x xml:space="preserve">Abstract</x> This study investigated whether children born in a second language (L2) environment pronounce their L2 with foreign accents and, if so, when foreign accents first emerge. This study also examined the latest age of onset (AO) of extensive L2 experience at which native L2 pronunciation is possible and explored several factors that affect the degree of perceived accent for child L2 learners. Participants included 20 native Finnish children and 19 Finnish‐born Turkish children 7–17 years of age (mean AO = 3) as well as 61 native Finnish raters who evaluated the speech samples for foreign accent using a 9‐point scale. Only 4 of the 19 Turkish children spoke Finnish without foreign accents, which were first detectable at an AO of 2.5 years. AO was the main determiner of perceived accent, followed by home use of first language (L1), and the amount of L2 and L1 use. These findings suggest that there is an interplay between AO and language use factors in determining child L2 learners' accent.